Adherence to antiretroviral therapy and symptom burden among people living with aids attending art clinic at BPKIHS. - Timilsina,Anuradha (2019)
ABSTRACT: Background: ART offers significantly improved management of symptoms though these benefits are dependent on adherence to a complex medication regimen. Likewise, high prevalence of troublesome symptoms is reported at all stages of HIV infection and persists during treatment. Objective: The objectives of this study were to assess the adherence to ART and symptom burden among people living with AIDS, to find out the association of adherence and symptom burden with selected variables and to find out the relationship between adherence and symptom burden. Materials and Methods: A descriptive cross sectional study was carried out among 112 of the patients living with AIDS receiving ART at BPKIHS for at least three months using convenient sampling technique.ACTG Questionnaire and MSAS Scale were used for data collection. Results: The mean adherence of the respondents was 91%.Only 64.3% of the respondents had optimal adherence to ART therapy. A total of 21.4% of the respondents had perceived significant symptom burden.Among variables, duration of illness, history of OI, use of aids for rememberance and keeping regular appointments were found to be significantly associated with ART adherence. Whereas, age, gender, marital status and health status during previous month were found to be significantly associated with Symptom burden, at 0.05 level of significance. Also, ART adherence was not found to be associated with Symptom Burden. Conclusion: This study revealed that more than half of the respondents had optimal adherence to ART and nearly one fourth of them had perceived significant symptom burden.Likewise,More than physical symptoms the psychological symptoms had cause more distress in the respondents Key Words: Adherence, PLWA, Symptom Burden